The development of shared mobility in Poland using the example of a city bike system - Puzio, Ewa (Rozwój współdzielonej mobilności w Polsce na przykładzie systemu roweru miejskiego, 2020)
The constant influx of people to cities is associated with the increase in the transport needs of urban residents. The consequences of these phenomena are the challenges posed to local governments in shaping urban mobility towards sharing transport means.The article discusses the development of shared mobility in Poland based on the example of a city bike system. The undertaken considerations are presented on the basis of the results of secondary research against the background of changes in the attitudes of the transport behaviour of residents consisting in the growing interest in the use of alternative methods of mobility. The aim of the paper is to indicate the factors influencing the development of shared mobility in Poland with particular emphasis on the city bike system. In order to achieve this goal, the desk research method was used, taking into account the available literature and results of secondary research on shared mobility and bike sharing services in Poland. The territory of Poland was used as the research area
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 162-170
Keywords: shared mobility; urban bike system; transport; współdzielona mobilność; system roweru miejskiego